2018
DOI: 10.1029/2018wr022606
|View full text |Cite
|
Sign up to set email alerts
|

A Ranking of Hydrological Signatures Based on Their Predictability in Space

Abstract: We used machine learning (random forests) and a hydrological model to simulate 15 hydrological signatures over 671 catchments in the US. The predictability of the signatures is highly correlated with the smoothness of their spatial pattern, which we quantified using Moran's I. Poorly-predicted signatures vary abruptly in space, are sensitive to streamflow errors and their links to catchment attributes are elusive. AbstractHydrological signatures are now used for a wide range of purposes, including catchment cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
244
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 206 publications
(263 citation statements)
references
References 85 publications
16
244
3
Order By: Relevance
“…The Soil Moisture Network sites are located in five different climate regions (CD, CW, CX, WD, WW; see Section 2 and Figure ). We make the following hypotheses, based on physical reasoning: Climate: Addor et al () used a large‐scale in the United States to show that climate metrics are a strong predictor for hydrologic signature values. In this study, we hypothesise that climate is the dominant factor for PDF type and seasonal transitions dates, both of which depend on the annual pattern of rainfall and evapotranspiration.…”
Section: Methodsologymentioning
confidence: 99%
See 1 more Smart Citation
“…The Soil Moisture Network sites are located in five different climate regions (CD, CW, CX, WD, WW; see Section 2 and Figure ). We make the following hypotheses, based on physical reasoning: Climate: Addor et al () used a large‐scale in the United States to show that climate metrics are a strong predictor for hydrologic signature values. In this study, we hypothesise that climate is the dominant factor for PDF type and seasonal transitions dates, both of which depend on the annual pattern of rainfall and evapotranspiration.…”
Section: Methodsologymentioning
confidence: 99%
“…1. Climate:Addor et al (2018) used a large-scale in the United States to show that climate metrics are a strong predictor for hydrologic signature values. In this study, we hypothesise that climate is the dominant factor for PDF type and seasonal transitions dates, both of which depend on the annual pattern of rainfall and evap-…”
mentioning
confidence: 99%
“…Yilmaz, Gupta, and Wagener (2008) and McDonnell et al (2007) look more generally for spatialtemporal patterns in the data that could be explained by differences in processes. Large-scale techniques, such as machine learning, random forests, and stepwise regressions, can elucidate the relationship of signature values with climatic and physical characteristics of watersheds, for example, Addor et al (2018) for the United States, Kuentz, Arheimer, Hundecha, and Wagener (2017) in Europe, and Trancoso, Phinn, McVicar, Larsen, and McAlpine (2017) in Australia. These studies found that climate was a dominant control on signatures, with Kuentz et al (2017) also finding that geology (for base flow) and land cover were important characteristics.…”
Section: Strengthening the Link Between Signatures And Processesmentioning
confidence: 99%
“…There are a variety of typical streamflow characteristics proven to be useful for model calibration, including the FDC, baseflow indices, runoff ratio, master recession curve (Addor et al, 2018;Fenicia et al, 2018;Troy et al, 2008;Winsemius et al, 2009;Yilmaz et al, 2008). Moreover, the experiments conducted by Fenicia et al (2018) showed that calibration against several FDC quantiles and baseflow index can produce virtually indistinguishable streamflow prediction from calibration operated directly on the streamflow time series.…”
Section: Parameter Calibration Strategymentioning
confidence: 99%